The velvet cage of reform: neoliberal discourses in Qatari education policy - Sellami, Abdellatif (Frontiers in Education, 2025)
This study employs Critical Discourse Analysis to examine how neoliberal rationalities are constructed and disseminated through Qatari education policy discourse. Drawing on a corpus of policy documents published between 2005 and 2025, the analysis identifies dominant themes of marketization, accountability, and global benchmarking. These discourses frame education primarily as an instrument of economic development, downplaying issues related to equity, inclusion, and alternative epistemologies. Evidence points to a hybrid policy logic: Qatari reforms simultaneously align with global neoliberal trends while selectively integrating national cultural references to secure public legitimacy. Anchored in the strategic goals of Qatar National Vision 2030, these reforms prioritize internationalization, performance-based governance, and labor market labor market responsiveness. However, the extent to which such reforms are shaped by neoliberal rationalities remains under-examined. This study critically interrogates how language constructs reform narratives, positions stakeholders, and legitimizes market-oriented governance. Findings reveal the dominance of technocratic discourses that privilege efficiency, standardization, and performativity, at the expense of educational justice and democratic participation. The analysis also exposes discursive tensions between global competitiveness and national identity, raising questions about the localization of transnational policy scripts in Qatar and the broader Gulf context. By foregrounding the ideological work of discourse, this study contributes to critical policy sociology and the global education reform literature, illuminating how neoliberalism operates not only through policy content but through the linguistic and epistemic structures that sustain it.